Patterning of Food Preferences Among Iranian Adults: Results from SEPAHAN Study - Moradi, Maedeh (Int J Prev Med, 2020)
BACKGROUND: The present study was conducted to evaluate the pattern of food preference among a large sample of Iranian adults. METHODS: In a cross-sectional study within the study on the epidemiology of psychological alimentary health and nutrition (SEPAHAN) projects, a total of 6239 of 8694 subjects completed a 106-item food preference questionnaire. Subjects indicated whether they liked, disliked or had gastrointestinal symptoms for each food item separately. They also reported the frequency of consumption for each food item. RESULTS: We observed that presence of some foods such as yogurt, fruits and vegetables in the list of the most preferred food items and presence of kalbas, sausages and chips in the list of the most disliked food items, were representative of healthy dietary pattern in this population. Results also revealed that women liked unhealthy foods more than men (P value <0.05 for all significant food items). Moreover, in most of the food items, men reported less gastrointestinal symptoms than women (P value <0.05 for all significant food items). Our findings revealed that smokers disliked most of the healthy food items. We also observed that pregnant women regardless of the trimesters, reported dislike for sweet-tasting food items. CONCLUSIONS: More researches are suggested in order to indicate the origins of preferences and recommend some practical alternatives to improve the dietary pattern in society.